Analysing the classroom environment: instrument creation, validation, and implementation - Rovira-Mañé, Marta; Camps Bansell, Jaume (Kuaapy Ayvu, 2024)
This scientific paper focuses on the creation of a new instrument to respond to the need to analyze the quality of the classroom environment of today's classrooms, and consequently, to be able to correct what is needed. Previous projects had some shortcomings due to the year they were published, such as the emergence of new technologies in the classroom, consequently a review and update seemed necessary. Therefore, a new instrument has been created that adapts to the current needs of students in the middle and upper cycle of primary school (8-12 years). All these characteristics that affect students have been assessed in five variables: interest and motivation, satisfaction, relationship between teacher and student, relationship among students and communication. After being validated, the tool has been implemented in 46 classrooms of schools with different characteristics and context. The results obtained have been analyzed and statistically validated by IBM SPSS program through Cronbach's alpha, which has ensured that there is consistency in each of the answers.